Reprint of "Preclinical and clinical effects of Coleus forskohlii, Salacia reticulata and Sesamum indicum modifying pancreatic lipase inhibition in vitro and reducing total body fat". (October 2015) - Badmaev, Vladimir; Hatakeyama, Yoshitaka; Yamazaki, Noriyuki; Noro, Akira; Mohamed, Faizal; Ho, Chi-Tang; Pan, Min-Hsiung
Highlights: C. forskohlii, S. reticulata and S. indicum showed different inhibitory effect on activity of pancreatic lipase. Three herb extracts treatment resulted in synergistic inhibited pancreatic lipase. Supplemented C. forskohlii decreased appetite. C. forskohlii significantly decreased caloric intake in the clinical study. Abstract: The herbal compositions of Coleus forskohlii, Salacia reticulata, and Sesamum indicum, standardized for forskolin, mangiferin, and sesamin, respectively, were shown, in vitro, to inhibit pancreatic lipase with differing degrees and dynamics. In the placebo controlled six weeks clinical study the daily intake of 1000 mg C. forskohlii stand-alone standardized for 10% forskolin, showed statistically significant lowering of total body fat vs. baseline and placebo group (p < 0.05). The computerized tomography showed decrease of total body fat and visceral fat in C. forskohlii group in comparison to the baseline. The potential of three herbal extracts preventing dietary fat absorption was emphasized by the in vitro synergy between C. forskohlii and S. reticulata inhibiting pancreatic lipase at higher rate than the fat-blocking activity generated by each component alone. The in vitro addition of S. indicum to the formula was found to synergistically assist inhibition of the pancreatic lipase in a lower dose range, while moderating the pancreatic lipase inhibition in a higher dose range. This dual mechanism of S. indicum was postulated as a safety mechanism preventing any potential side effects resulting from excessive inhibition of pancreatic lipase activity.